O COTIDIANO DA ESCOLA DE EDUCAÇÃO ESPECIAL NA VISÃO DE PROFESSORES APÓS A RESOLUÇÃO SEED/PR 3600 DE 2011 - HYKAVEI JUNIOR, PAULINO (2016)
Research on school inclusion and special education are extremely important to the educational scenario we have today. When done, solutions and problems are encountered in that the entire process is performed so arranged and complete. Even after several years of empirical knowledge acquired studies and discussions should happen to get further information about the chosen subject. Special education is an area which aims to meet students who have a disability, this mode in the state of Paraná has become as part of basic education, and changes in planning and teaching practices. This study had as main objective to understand ma opinion five teachers who work in special education the changes in these institutions. Interviews were conducted addressing the issues that have been defined at the beginning of the research. These themes aimed to understand what the work of these teachers before and after the changes made in the state of Parana and how is the work of the same within the institution and their role in the school inclusion. We had such results that the work of these teachers underwent minor changes in their practices that work continues as it was before the Special Education change. On the process of including all stated that require changes in the common schools to receive students with disabilities and that some students who attend special education can not afford to attend the regular education because of their commitment. We conclude that the school inclusion requires a proximity of Special Education, understanding the process as a whole by encouraging the student with Special Education is enrolled in regular education. And that Special Education needs information on the importance of inclusion of students with disabilities in regular education. Thus we understand that studies for this purpose must be submitted so that we can disseminate and understand the inclusion and special education process.